Discoloration Effects of High-Dose γ-Irradiation and Long-Term Thermal Aging of (U)HMW-PE. (6th September 2017) - Kömmling, Anja; Chatzigiannakis, Emmanouil; Beckmann, Jörg; Wachtendorf, Volker; von der Ehe, Kerstin; Braun, Ulrike; Jaunich, Matthias; Schade, Ulrich; Wolff, Dietmar
Abstract : Two polyethylene types with ultra-high (UHMW-PE) and high molecular weight (HMW-PE) used as neutron radiation shielding materials in casks for radioactive waste were irradiated with doses up to 600 kGy using a 60 Co gamma source. Subsequently, thermal aging at 125°C was applied for up to one year. Degradation effects in the materials were characterized using colorimetry, UV-Vis spectroscopy, IR spectroscopy, and DSC. Both materials exhibited a yellowing upon irradiation. The discoloration of UHMW-PE disappeared again after thermal aging. Therefore, the yellowing is assumed to originate from annealable color centers in the form of free radicals that are trapped in the crystalline regions of the polymer and recombine at elevated temperatures. For the antioxidant-containing HMW-PE, yellowing was observed after both irradiation and thermal aging. The color change was correlated mainly to decomposition products of the antioxidant in addition to trapped radicals as in UHMW-PE. Additionally, black spots appeared after thermal aging of HMW-PE.